Examining Women, Peace, and Security Agenda in Local Concept Case study: Aceh, Indonesia - Ocktaviana, Sentiela; Kamaruzzaman, Suraiya (Jurnal Masyarakat dan Budaya, 2021)
The UN security council established Resolution 1325 (SCR1325) to affirm women’s vital role in peacemaking and peacebuilding in conflict. Women, Peace, and Security (WPS) agenda emphases equal participation of men and women in the negotiation process and creates gender equality in post-conflict, and eradicates gender violence in conflict. This study illustrates how women in Aceh fight for their rights throughout the conflict and post-conflict within an unequal society; and also highlights how important to adapt the WPS agenda to ensure gender equality and social justice. By applying narrative analysis, researchers enable to explore Acehnese women’s experiences and struggles in seeking justice through their narratives. The implementation of the WPS agenda in Aceh faces many challenges, both structural and cultural. Thegovernment and combatant groups overlooked women’s participation in peace negotiation. When the conflict ended, gender inequality is still lingering in every aspect. Aceh women experience injustice, sexual violence, and discrimination in the domestic and public sphere. Besides revealing the challenges in adapting the WPS agenda and creating gender equality in Aceh, this study also obtains policy recommendations to be considered by the local and central governments to ensure gender justice and substantial peace for women in Aceh post-conflict.